The Value in Verifying Medical Folklore - Dennis J., Baumgardner (Aurora Health Care, 2018)
Citing a related article published within this issue of the Journal of Patient-Centered Research and Reviews, the author opines on why traditional ideas regarding human health can persist over decades, and even centuries, despite a lack of scientifically accumulated evidence. It is important to keep in mind that some commonly accepted truths are supported by little to no factual data, and that occasionally patients may benefit from clarification on what is (or, often, is not) actually known about longstanding “rules of thumb” (eg, certain home remedies, disease-prevention measures or behavioral concerns). On the flip side, traditions that are shown to be not harmful, like drinking chicken soup to relieve cold symptoms, may be safely indulged regardless of effectiveness.